The Relationship Between Beta-Blockade, Plasma Potassium Concentrations and Muscle Excitability Following Static Exercise - Unsworth, Karen L. (My University, 1996)
Abstract Not Provided.
Keywords: beta-blockade, plasma potassium concentrations, muscle excitability, static exercise